2021
DOI: 10.3390/jcm10245957
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intramedullary Magnetic Nail, Monolateral External Distractor, and Spatial External Fixator in Femur Lengthening in Adolescents with Congenital Diseases

Abstract: The aim of this study is to evaluate the course of the treatment and clinical and functional outcomes of femur lengthening in adolescents with congenital disorders by the application of different surgical methods. This retrospective study comprised 35 patients (39 procedures). A total of 11 patients underwent femur lengthening with the use of the intramedullary magnetic nail (IMN) Precise 2 (NuVasive, San Diego, CA, USA), 7 patients (11 procedures) with the use of the monolateral external distractor Modular Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In IM fixation, the contact surface in the osteotomy line increases, which provides a shorter healing time compared to other methods [21]. Pietrzak et al demonstrated that IM nailing is the best option for femoral length disorder compared to a monoliteral external distractor and external fixator [22]. Antegrade IM femoral nailing with distal hemiepiphysiodesis is a very promising therapeutic option when young patients require correction of deformity and limb lengthening [23].…”
Section: Discussionmentioning
confidence: 99%
“…In IM fixation, the contact surface in the osteotomy line increases, which provides a shorter healing time compared to other methods [21]. Pietrzak et al demonstrated that IM nailing is the best option for femoral length disorder compared to a monoliteral external distractor and external fixator [22]. Antegrade IM femoral nailing with distal hemiepiphysiodesis is a very promising therapeutic option when young patients require correction of deformity and limb lengthening [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies show that the actual distraction rate achieved is less than that and ranges from 0.5 -0.8 mm/day. [26][27][28][29] Balci et al found that the lengthening speed of 0.56 mm/day is optimal for lengthening in congenital tibial dysplasia. 30 We also reported a mean distraction rate of 0.73 mm/day and found that a distraction rate < 0.7 mm/ day results in almost statistically strong odds of achieving good HI.…”
Section: Original Article Smjmentioning
confidence: 99%
“… 25 In a retrospective comparative study of 75 children from 10 to 18 years of age undergoing lengthening in femurs without axial deformity, fewer adverse events were observed with internal lengthening nails than external fixation. 27 In 50 children between 11 and 17 years of age, femoral lengthenings were compared between external fixation and motorized nails. 28 Patients were matched for age and indication for lengthening, and more complications were found with external fixation.…”
Section: Internal Nail Lengtheningmentioning
confidence: 99%